MANAJEMEN WISATA RELIGI DI TARUTUNG - Siahaan, Meilani Lida; Panjaitan, Pernando; Harefa, Yestin (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
Salib Kasih is a Christian spiritual tourism site located in Siatas Barita, North Tapanuli, North Sumatra. This spiritual tourism was built to commemorate the services of Christian missionary from Germany, Ingwer Ludwig Nommensen, who started his mission in the Batak land. Salib Kasih covers an area of 7.00 km2 and has adequate facilities such as prayer rooms, parking lots, souvenir shops, and toilets. The management of religious tourism in Salib Kasih is the focus of this study. The management of religious tourism in Salib Kasih is carried out by the local government in collaboration with the surrounding community as the managers. The local government facilitates the management of this tourism by providing financial and technical support so that Salib Kasih can be well maintained and managed. The management of religious tourism in Salib Kasih is carried out through several management strategies, including promotion, tourism product development, facility development, and human resource training. Promotion strategy is carried out by marketing this tourism object through various media such as brochures, banners, and the official Salib Kasih website. Tourism product development is carried out by presenting various activities at Salib Kasih, such as retreats, seminars, and other religious events. Facility development is carried out by improving existing tourism facilities, such as toilets and parking areas. Human resource training is carried out by providing training and education to the surrounding community as tourism managers in Salib Kasih. In managing the religious tourism management in Salib Kasih, good cooperation is needed between the local government, the surrounding community, and the visitors of this tourism object. With good cooperation, Salib Kasih can be well maintained and managed, thus becoming an attractive tourism destination and providing benefits to the surrounding community. As an important Christian spiritual tourism object in North Tapanuli, Salib Kasih has great potential for further development and providing benefits to the surrounding community.